The effect of Islamic financial literacy, digital marketing and brand image on customer loyalty of Indonesian Sharia Bank in Garut Regency - Nauval Putra Ridha Rabbani; Eti Kusmiati; Dioka Muhammad Akbar (Universitas Nusa Cendana, 2026)
In an increasingly competitive Islamic banking industry, customer loyalty has become a critical determinant of sustainable organizational performance. Understanding the factors that drive customer loyalty is therefore essential for Islamic financial institutions seeking to strengthen their market position. This study examines the influence of Islamic financial literacy, digital marketing, and brand image on customer loyalty among customers of Bank Syariah Indonesia in Garut Regency, Indonesia. Employing a quantitative research design with an associative approach, the study utilizes Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the relationships among the proposed constructs. The findings reveal that Islamic financial literacy, digital marketing, and brand image each exert a positive and significant influence on customer loyalty. Customers with a stronger understanding of Islamic financial principles are more likely to demonstrate loyalty toward Islamic banking services. Furthermore, effective digital marketing strategies enhance customer engagement and strengthen long-term relationships, while brand image emerges as the most influential determinant of customer loyalty. These results highlight the importance of integrating educational, technological, and branding strategies to foster customer retention in the Islamic banking sector. The study contributes to the growing literature on Islamic banking by providing empirical evidence that customer loyalty is shaped by both cognitive and experiential factors in the digital era. The findings offer practical implications for Bank Syariah Indonesia and other Islamic financial institutions in designing customer-centric strategies aimed at enhancing loyalty and sustaining competitive advantage. Keywords: Islamic Financial Literacy; Digital Marketing; Brand Image; Customer Loyalty